Digital Marketing Strategy for MSME Products 'Ketan Ma Adah Bagendit' by Utilizing Social Media - Firman Nur Hakim; Abda Fillah Al Intifadha; Agni Triwulansari; Ahmad Yusron Sidik; Aliefa Bintan Karamy; Elsa Zulfiah; Aam Munawar; Gita Anggaeni Permana; Imas Kurniati; Mohamad Rifki Nawawi; Nabila Yuniawati; Nawadhir Fauzan; Neneng Lisna Rahayu Sidiq; Rifa Fardila Arti; Rizki Insani Saputra; Romi Fikriawan Agusty; Wiwit Nursafitri; Nizar Alam Hamdani (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract This community service has a purpose or work program to provide motivation or education about the importance of digital marketing at this time. The method used is in the form of socialization and data collection of SMEs in Bagendit village which allows for assistance in Digital Marketing. The socialization was carried out by coming to a recitation event in each citizens association and then giving a lecture about the importance of Digital Marketing. Then the data collection was carried out after the lecture by having a dialogue with the mothers who were present at the recitation. The results of this dedication to a work program are expected to be more productive on a daily basis, besides that it is also expected to be able to apply this digital marketing to SMEs owned so that they are more widely known. Abstrak Pengabdian kepada masyarakat Kelompok 1 ini memiliki tujuan atau program kerja untuk memberikan motivasi atau edukasi tentang pentingnya Digital Marketing pada saat sekarang ini. Metode yang digunakan berupa sosialisasi dan pendataan UMKM yang ada pada desa Bagendit yang memungkinkan untuk dibantu dalam Digital Marketingnya. Sosialisasi dilakukan dengan cara datang ke acara pengajian di setiap RW lalu memberikan ceramah tentang pentingnya Digital Marketing. Lalu untuk pendataan dilakukan sesudah ceramah dengan cara berdialog dengan ibu ibu yang hadir pada pengajian tersebut. Hasil dari pengabdian pada suatu program kerja ini diharapkan agar lebih bisa produktif dalam sehari harinya selain itu juga diharapkan dapat mengaplikasikannya digital marketing ini untuk UMKM yang dimiliki agar terkenal lebih luas.